Experimental evaluation of the sealing ability of MTA and cold ceramic by using bacterial leakage method - Fatemeh Mokhtari; Kazem Koopaei; Jalil Modaresi; Hamid Reza Hemati; Hengameh Zandi (Tehran University of Medical Sciences, 2017)
Background and Aims: The purpose of this study was to evaluate the sealing ability of MTA and cold ceramic by using bacterial leakage method. Materials and Methods: In this experimental study, fifty human single root extracted teeth were chosen. In group A, 20 teeth were filled with MTA and in group B, 20 teeth were filled with cold ceramic. Five teeth were used as a positive control (obturated using gutta-percha without sealer), and five teeth were used as negative control (obturated using gutta-percha with AH26 sealer and coated with two layers of nail varnish). A bacterial leakage model utilizing Enterococcus faecalis was used for evaluation of the sealing ability. The teeth were placed in test tubes, so that they formed two upper and lower compartments. The cultured bacteria in the upper chamber were in contact with the coronal area of the tooth. The root end was placed in the lower chamber containing sterile culture media. In this case, the filling of the root canal was only the communication path between the upper and lower chambers. In this method, the presence of turbidity in the lower chamber indicated that bacteria had penetrated through barrier and reached the medium. The leakage was measured. The acquired data was analyzed using Chi-square test. Results: In group A (MTA), 7 samples and in group B (Cold ceramic), 4 samples should the leakage. In regarding the leakage, there was no statistically significant difference between MTA and cold ceramic. (P=0.288) Conclusion: The results showed that the sealing ability of MTA and cold ceramic was similar as root filling materials.